2000
DOI: 10.1590/s0100-204x2000000100023
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do tamanho do folículo na maturação nuclear e citoplasmática de ovócitos de fêmeas zebuínas

Abstract: RESUMO -Este estudo avaliou o efeito do tamanho do folículo na capacidade dos ovócitos de sofrerem maturação nuclear e citoplasmática. Ovários de vacas Nelore (Bos indicus) foram coletados logo após o abate, e os complexos cúmulus-ovócitos foram aspirados de folículos de diferentes categorias, e classificados de acordo com seus diâmetros em: 1-2 mm, 3-5 mm, 6-8 mm e ≥9 mm. A medida do diâmetro e a fixação dos ovócitos para avaliação do estádio nuclear antes da maturação foram feitas logo após a aspiração. Ovóc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
1
0
1
Order By: Relevance
“…The results showed that, at 0 h of maturation, there was a higher percentage of oocytes from follicles of 6-8 mm in GV compared with the other groups. Despite the significant difference, this has little biological significance, because all of the groups showed more than 90% of the oocytes at the GV stage, which is consistent with other findings in the literature (Dode et al, 2000;Dode & Adona, 2001). At 8 h of maturation, the control group was more advanced in meiosis than the other groups.…”
Section: Discussionsupporting
confidence: 86%
“…The results showed that, at 0 h of maturation, there was a higher percentage of oocytes from follicles of 6-8 mm in GV compared with the other groups. Despite the significant difference, this has little biological significance, because all of the groups showed more than 90% of the oocytes at the GV stage, which is consistent with other findings in the literature (Dode et al, 2000;Dode & Adona, 2001). At 8 h of maturation, the control group was more advanced in meiosis than the other groups.…”
Section: Discussionsupporting
confidence: 86%
“…Maturational competence is progressively acquired during follicular growth through a range of cellular and molecular attributes that provide the oocyte with the ability to complete meiosis, be fertilized and undergo embryonic development. Therefore, reaching metaphase II of meiosis is only one aspect of maturation and does not necessarily signal oocyte competence (Crozet et al, 1995;Dode et al, 2000). The results from our laboratory have shown that oocytes from smaller follicles (1 -3 mm) have a smaller diameter and that oocyte size did not change after the follicles had reached 3 mm in diameter.…”
Section: Discussionmentioning
confidence: 88%
“…A PIV envolve três etapas consecutivas: a maturação in vitro (MIV) de ovócitos, fecundação in vitro (FIV) e o cultivo in vitro (CIV) de embriões. A MIV é uma das fases mais críticas do processo, pois envolve a capacidade do ovócito em completar a meiose, bem como alterações bioquímicas, estruturais e citoesqueléticas que serão importantes para a fecundação e desenvolvimento embrionário subsequente (DODE et al, 2000;BERTAGNOLLI et al, 2004;DADARWAL et al, 2015). O processo de maturação ovocitária inclui alterações nucleares e citoplasmática, que são eventos distintos, porém interligados.…”
Section: Introductionunclassified